1446. Dynamics of Enterococcus faecalis Cardiolipin Synthase Gene Expression Reveal Compensatory Roles in Daptomycin Resistance. (31st December 2020) - Nguyen, April; Polamraju, Vinathi; Tran, Truc T; Panesso-Botero, Diana; Khan, Ayesha; Mileykovskaya, Eugenia; Vitrac, Heidi; Arias, Cesar A
Abstract: Background: Daptomycin (DAP) is a lipopeptide antibiotic targeting membrane anionic phospholipids (APLs) at the division septum, and resistance (DAP-R) has been linked to mutations in genes encoding i ) the LiaFSR stress response system or its effector LiaX, and ii ) cardiolipin synthase (Cls). Activation of the E. faecalis (Efs ) LiaFSR response is associated with DAP-R and redistribution of APL microdomains away from the septum, and cardiolipin is predicted to be a major component of these APL microdomains. Efs harbors two putative cls genes, cls1 and cls2 . While changes in Cls1 have been implicated in DAP-R, the exact roles of each enzyme in resistance are unknown. We aim to characterize the contributions of Cls1 and Cls2 in the development of DAP-R. Methods: cls1 and cls2 were deleted individually and in tandem from DAP-S Efs OG117 and DAP-R Efs OG117∆ liaX (a DAP-R derivative strain with an activated LiaFSR response). Mutants were characterized by DAP minimum inhibitory concentration (MIC) using E-test on Mueller-Hinton II agar and localization of APL microdomains with 10-N-nonyl-acridine orange staining. Quantitative PCR (qRT-PCR) was used to study gene expression profiles of cls1 and cls2 in Efs OG117∆ liaX relative to Efs OG117 across the cell growth cycle. Results: qRT-PCR revealed differential expression profiles of cls1 and cls2 associated with DAP-R. cls1 was highly upregulated in stationary phase concurrent with a decrease in cls2 expression. However, independent deletion of cls1 or cls2 in the DAP-R background resulted in no significant changes in DAP MICs or localization of APL microdomains (remaining non-septal). Further studies revealed that cls2 expression is upregulated upon deletion of cls1 in both the DAP-S and DAP-R background, suggesting a potential compensatory role for Cls2. Double deletion of both cls genes in the DAP-R strain decreased DAP MIC and restored the septal localization of APL microdomains. Conclusion: Cls1 is the major and predominant enzyme involved in cell membrane adaptation associated with the development of DAP-R in E. faecalis . However, we describe a novel compensatory and overlapping role for cardiolipin synthases to ensure bacterial survival upon attack from antimicrobial peptides and related antibiotics. Disclosures: Cesar A. Arias, MD, MSc, PhD, FIDSA, Entasis Therapeutics (Scientific Research Study Investigator)MeMed (Scientific Research Study Investigator)Merck (Grant/Research Support)